2012
DOI: 10.1111/j.1471-4159.2012.07681.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to trophic neurite outgrowth of sensory neurons exposed to insulin

Abstract: J. Neurochem. (2012) 121, 263–276. Abstract Insulin offers trophic support through receptors expressed widely on peripheral neurons. In this work, we studied whether peripheral sensory neurons demonstrate resistance to its trophic properties, a property relevant during type 2 diabetes mellitus or following supraphysiological therapy. Insulin receptors were not only localized to neuronal membranes and cytoplasm but also had a unique, previously unrecognized localization to neuronal nuclei. We confirmed that nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 50 publications
(96 reference statements)
4
53
0
Order By: Relevance
“…In the present study, we show that IRS-1-stimulated N-Myc expression may trigger the apoptosis of neuronal cells and the inhibition of neurite outgrowth in brains with HFD-induced I/R. One study demonstrated that the I/R leads to the neurite outgrowth's inhibition of sensory neuron in vitro Resistance to trophic neurite outgrowth of sensory neurons exposed to insulin (Singh et al, 2012). In the present study, we confirmed the morphological changes including reduced neurite length in N2A cells under I/R condition.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the present study, we show that IRS-1-stimulated N-Myc expression may trigger the apoptosis of neuronal cells and the inhibition of neurite outgrowth in brains with HFD-induced I/R. One study demonstrated that the I/R leads to the neurite outgrowth's inhibition of sensory neuron in vitro Resistance to trophic neurite outgrowth of sensory neurons exposed to insulin (Singh et al, 2012). In the present study, we confirmed the morphological changes including reduced neurite length in N2A cells under I/R condition.…”
Section: Discussionsupporting
confidence: 53%
“…Several in vivo studies using HFDfed animal models have found that disruption of insulin action in the brain results in impaired memory function and cognitive decline (McNeilly et al, 2011;Arnold et al, 2014). Neurite outgrowth, which is involved in cognitive function (Singh et al, 2012), is also impaired in the brains of HFD-fed animals (Hashikawa-Hobara et al, 2012). Moreover, it is known that insulin signaling is related both to impaired memory function in diabetic dementia (Grote et al, 2011) and to neuronal apoptosis (Wilk et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Not only is the blood glucose level per se relevant, but also the level of insulin, which may have a trophic support [37] making the use of different models relevant. In STZ-induced diabetes, the beta cells are destroyed by the toxic effect of STZ and in the BB rats autoimmune mechanisms that destroy beta cells are in action [38].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin receptors (IRs) and receptor substrate scaffolds (IRS1, IRS2) are expressed by sensory neurons and activate signal transduction pathways that modulate neurite outgrowth and axonal plasticity (Fernyhough et al, 1993; Grote et al, 2013; Huang et al, 2005; Singh et al, 2012). In neurons, the insulin receptor pathway activates several messengers that include the important survival kinase, phosphatidylinositide 3-kinase (PI3-K), that is directly associated with, and activated by, IRS-1 and induces Akt activation (Grote, et al, 2013; Huang, et al, 2005; Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%